Characteristics of Patients, Self-Efficacy and Quality of Life among Patients with Type 2 Diabetes Mellitus - Karina Megasari Winahyu; Revi Anggita; Giri Widakdo (Jurnal Keperawatan Padjadjaran, 2019)
Diabetes mellitus as a chronic disease requires a long-term care, which influence the quality of life (QOL). A mechanism perceived by the patients who engage in long-term treatment, such as self-efficacy (SE) is prerequisite for the success of disease management. The study aimed to identify the relationship between characteristics of patients, SE and domains of QOL among patients with type 2 diabetes mellitus (T2DM) living in community. The study used a correlational analytical with a cross-sectional approach and recruited 105 patients with type 2 diabetes in Sukasari Public Health Center, Tangerang. Self-administered questionnaires were used to measure sociodemographic of T2DM patients, while the Diabetes Management Self-Efficacy Scale (DMSES) UK and Asian Diabetes Quality of Life (Asian DQOL) were used to measure SF and QOL, respectively. Data were analyzed using Spearman Rank-Order Correlation. The study revealed that characteristics of patients, including age and period of illness were negatively associated with memory and cognition domains of QOL, while years of education positively associated interpersonal relationship domains of QOL. For SE, it was positively significant associated with diet habit, energy, and financial aspects domains of QOL. The SE was positively associated with the QOL (r=0.31; p-value ≤ 0.01). The SE is relationship with QOL of T2DM. Therefore,  health care provider should need to maintain the domains of QOL through improving SE, while considering the characteristics of T2DM patients, including age, period of illness, and years of education.